Acoustic Emission as Method of Chatter Detection in Cutting - Shamarin N. N. Nikolay Nikolaevich; Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Podgornykh O. A. Oleg Anatolievich; Filippova E. O. Ekaterina Olegovna; Vorontsov A. V. (2018, 2018)
Title screen